The political culture of the vanguard or the construction of the revolutionary ethos. Cuba 1952-1959 (Tzintzun, Revista de Estudios Históricos, 2016)
Since the coup led by Fulgencio Batista on March 10, 1952, began a process ofreadjustment in the Cuban political structure which will culminate in 1959. Theroots of the Cuban revolution bom of national dynamic that is articulated in atleasttwo fronts: one, concerning the formation of political groups in tone insurrectionaryart, conceived and organized outside the established political parties in Cubanparliamentary system, and two, the formulation of a new political discourse thatjustified the creation of avant-garde groups and insurrectionary strategy. Here is,also the origin of the political culture that will define the Castro and revolutionaryideology, long before the emergence of the Cuban communists and their allegedinfluence on the development of the Cuban revolution and historiography claimssupported by the paradigm of Cold War.
Keywords: insurrection; vanguard; Castrismo; Cuban revolution